Live Birth from the Transfer of a Severely Fragmented Embryo Observed by Morphokinetics. (19th July 2018) - Lahav-Baratz, S.; Blais, I.; Koifman, M.; Ishai, D.; Wiener-Megnazi, Z.; Peer, G.; Dirnfeld, M.
Abstract : We report a live birth from a heavily fragmented embryo which continued cleavage to a fully expanded blastocyst. A 32-year-old patient underwent 2 IVF cycles without achieving pregnancy. In the first cycle, 2 embryos with fragmentation were transferred; in the second, all embryos were fragmented and no embryo transfer was performed. In a third cycle, 12 oocytes were retrieved and 11 of them were fertilized. On day 2, all 11 embryos started to unwind to fragments. By careful annotation, using the time-lapse EmbryoScope, we observed that one embryo continued division as expected, discarding all fragments aside. On day 5, this embryo showed promising annotation according to our lab model. The embryo was transferred into the uterus and resulted in the birth of a healthy baby at term. To our knowledge, this is the first case report assisted by EmbryoScope where a healthy baby was delivered from a fragmented embryo.